Effect of manganese and cadmium on biological attributes of wild water spinach (Ipomoea aquatica Forssk.) - Guan, Billy Teck Huat (2017)
Heavy metals are inorganic pollutants that are hazardous and toxic to the environment. Agricultural activities have indirectly introduced heavy metals peculiarly manganese (Mn) and cadmium (Cd) to the ecosystem and eventually have polluted aquatic ecosystem which included the ponds located in Universiti Putra Malaysia. Water pollution caused by the heavy metals can greatly affect the life of the wild water spinach (Ipomoea aquatica Forssk.), an edible aquatic plant that is living in the ponds. Consequently, human health can be threatened when the metal-contaminated wild water spinach was foraged for consumption. Hence, the metals effects of Mn and Cd on the health status, growth, anatomy, and DNA quality of the wild water spinach were studied. Furthermore, the metal uptake ability by the wild water spinach was determined. The metal bioavailability and health risk were also assessed upon consumption of the metal-contaminated wild water spinach. The mature wild water spinach was hydroponically cultivated under greenhouse conditions and was subjected to Mn and Cd treatments which included low treatment (0.30 mg/L for Mn and 0.10 mg/L for Cd), high treatment (1.50 mg/L for Mn and 0.50 mg/L for Cd), and the control (distilled water) for seven days. ANOVA analysis indicated that significant reduction was observed for roots length and surface area, shoots length, leaves surface area in the metal-contaminated wild water spinach with the increasing Mn and Cd concentrations (p < 0.05). Toxicity symptoms such as chlorosis and necrosis also occurred on the wild water spinach from the metal exposure. In the cellular level, the xylem, phloem, epidermis, parenchyma, sclerenchyma, and cell walls of the cross-sectional and longitudinal roots, stems, and leaves have experienced breaking and changes in size, shape, and arrangement that were induced by the metal accumulation. ANOVA results showed that the leaves’ DNA concentrations were significantly reduced ranging from 67.73 to 195.54 ng/μL and 56.10 to 212.05 ng/μL at higher Mn and Cd concentrations; similarly to the changes in DNA purity (p < 0.05). The ANOVA statistics showed that the removal efficiency, water-to-shoot bioaccumulation factor (BAF), and root-to-shoot translocation factors (TF) was significantly reduced at higher Mn concentrations (p < 0.05). The highest concentration of Mn and Cd was found in the dried (DHS) and raw (RHS) shoots with the highest slope values of 3.75 and 19.50, respectively. Both Mn and Cd had the highest bioaccessibility for absorption in the gastric phase (slope values = 9.68 and 28.28) than intestinal phase (slope values = 0.24 and 17.99). The health risk index showed values > 1, indicated that the raw (RHS) and cooked (CHS) wild water spinach contaminated with Mn and Cd were not safe to be consumed for the studied population in Selangor, Malaysia. As conclusion, impacts of Mn and Cd were clearly seen when changes occurred in the health status, growth, histological structure, and DNA quality of the metal-contaminated wild water spinach. These metals absorbed in the human gastrointestinal tract could eventually cause health hazards when consuming the metal-contaminated wild water spinach as demonstrated in this work. Nevertheless, wild water spinach can serve as an alternative for phytoremediation on metals-contaminated aqueous medium due to its fairly good metal uptake ability.